Factors Shaping Brand Awareness of Sumba Weaving Products in a Phenomenological Perspective - Sari, Wulan Purnama; Mei Ie, Mei Ie; Tunjungsari, Hetty Karunia (Jurnal Komunikasi, 2021)
The fashion industry is included in the top three creative industry sectors in Indonesia. The development of the fashion industry is also supported by various parties and is also enlivened by the distinctive fashion of Indonesian traditional fabrics. Several traditional Indonesian fabrics, such as batik, lurik, Lombok songket have successfully penetrated the international market, so the opportunity to continue developing the fashion industry with traditional fabrics is still large. One of them is to use a typical Sumba woven cloth which is not gaining popularity with Sumba as a tourist destination. Therefore, this research was conducted with the aim of digging deeper into the factors that shape the brand awareness of Sumba woven fabrics. This research was conducted using a qualitative approach and phenomenological methods, with data collection using the Focus Group Discussion (FGD) technique. The results showed that the factors that formed brand awareness of Sumba woven fabrics were divided into two, namely internal and external factors. Internal factors are factors that come from the product itself, such as motif, price, color, age of fabric, quality, craftsmen. While external factors come from outside the product, including the power of word of mouth, organizing events (exhibitions), government involvement (regional and central), and showing the identity of the wearer. Industri fashion termasuk dalam tiga besar sektor industri kreatif di Indonesia. Perkembangan industri fashion ini juga didukung berbagai pihak, serta turut diramaikan dengan fashion khas kain tradisional Indonesia. Beberapa kain tradisional Indonesia, seperti batik, lurik, songket Lombok telah berhasil menembus pasar internasional, sehingga peluang untuk terus mengembangkan industri fashion dengan kain tradisional masih besar. Salah satunya adalah dengan menggunakan kain tenun khas Sumba yang kurang mendapatkan popularitas dengan Sumba sebagai destinasi wisata. Oleh karenanya, penelitian ini dilakukan dengan tujuan untuk menggali lebih dalam mengenai faktor yang membentuk brand awareness kain tenun Sumba. Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif dan metode fenomenologi, dengan pengumpulan data menggunakan teknik Focus Group Discussion (FGD). Hasil penelitian menunjukkan bahwa faktor yang membentuk brand awareness atas produk kain tenun Sumba dibedakan menjadi dua, yaitu faktor internal dan eksternal. Faktor internal merupakan faktor yang berasal dari produk sendiri, seperti motif, harga, warna, usia kain, kualitas, pengarajin. Sedangkan faktor eskternal berasal dari luar produk, meliputi kekuatan dari word of mouth, penyelenggaraan event (pameran), keterlibatan pemerintah (daerah dan pusat), dan menunjukkan identitas pemakainya.